Type 2 diabetes is associated with a higher incidence of hospitalization for pulmonary embolism in Spain: Analysis of hospital discharge data during 2004–2013. Issue 7 (4th July 2016) - de Miguel‐Díez, Javier; Muñoz‐Rivas, Nuria; Jiménez‐García, Rodrigo; Hernández‐Barrera, Valentín; Carrasco‐Garrido, Pilar; Monreal, Manuel; Jiménez, David; Guijarro, Ricardo; López de Andrés, Ana
ABSTRACT: Background and objective: We compared the incidence and outcome of pulmonary embolism (PE) in individuals with and without type 2 diabetes mellitus (T2DM) in Spain during 2004–2013. Methods: The study was based on National Hospital Discharge Data, and the study population comprised patients hospitalized for PE. Annual incidence rates were classified according to T2DM status. In‐hospital mortality (IHM), length of hospital stay (LOHS), comorbidities and use of diagnosis and therapeutic procedures were analysed. Results: We identified 123 872 discharges of patients (56 361 men and 67 511 women) with PE as their primary diagnosis (15.3% with T2DM). Incidence of discharge diagnoses of PE increased significantly in all groups. Crude rates were higher in diabetic patients. A positive association was identified between T2DM and PE: adjusted IRR was 2.00 (95% CI: 1.95–2.05) for men and 2.50 (95% CI: 2.45–2.57) for women. LOHS, readmissions and IHM decreased significantly for both groups. An association between IHM and risk factors (older age, Charlson comorbidity index >3, atrial fibrillation and cancer) was observed. T2DM was associated with higher IHM in men (OR: 1.22, 95% CI: 1.12–1.32) and women (OR: 1.24, 95% CI: 1.15–1.33). The use of computed tomography pulmonary angiography increased significantly overtime. Conclusion: We confirmed that in both men and women, diabetes was an independent risk factor for IHM. The incidence of discharge of patients with PE increased significantly during the study period. Diabetic men and women had a higher risk of hospitalization for PE than non‐diabetic men and women. Diabetic women had higher IHM than diabetic men. Abstract : The incidence of the discharge diagnoses of pulmonary embolism (PE) increased in type 2 diabetic and non‐diabetic patients in Spain during 2004–2013. After adjustment for confounders, the incidence of PE in diabetic men and women was 2.00 and 2.50 times higher than in non‐diabetic men and women.